PANCASILA-BASED EDUCATIONAL CONTENT ON SOCIAL MEDIA AS AN EFFORT TO OVERCOME THE MORAL DEGRADATION OF THE MILLENNIAL GENERATION DURING PANDEMIC - Prastiwi, Duwi Adinda; Pandin, Moses Glorino Rumambo (Ganesha Civic Education Journal, 2023)
The COVID-19 pandemic is currently attacking Indonesia and encouraging an increase in internet consumption, especially social media. Freedom to access information can have both positive and negative impacts on the millennial generation. One of the negative impacts is moral decline or moral degradation. This article aims to find out how to overcome moral degradation among the millennial generation through Pancasila-based educational content. The method used is literature review by searching for journal articles from Google Scholar and ebooks from 2019 to 2021. By combining several keywords, the author formulates several research questions: (a) what are millennials and social media? (b) how the impact of social media on the moral character of the millennial generation?, and (c) how to overcome moral degradation among the millennial generation? Based on the analysis of research findings, ten journals met the inclusion of reviews based on research content. This research is motivated by the moral degradation of the millennial generation as a negative impact of the use of social media. The ten articles collected show that creating educational and informative content based on Pancasila can overcome moral degradation on social media. In addition, media literacy can also overcome moral degradation.